Dopamine and the Biology of Creativity: Lessons from Parkinson’s Disease - Lhommée, Eugénie; Batir, Alina; Quesada, Jean-Louis; Ardouin, Claire; Fraix, Valérie; Seigneuret, Eric; Chabardès, Stéphan; Benabid, Alim-Louis; Pollak, Pierre; Krack, Paul (Frontiers in Neurology, 2014)
BACKGROUND: Parkinson’s disease (PD) is characterized by reduced flexibility, conceptualization and visuo-spatial abilities. Although these are essential to creativity, case studies show emergence of creativity during PD. Knowledge about the role of dopamine in creativity so far only stems from a few case reports. We aim at demonstrating that creativity can be induced by dopaminergic treatments in PD, and tends to disappear after withdrawal of dopamine agonists. METHODS: 11 consecutive creative PD patients were selected from candidates for subthalamic deep brain stimulation (STN DBS) surgery, and compared to 22 non-creative control PD patients. Motor disability (UPDRS III), cognition (Frontal Score, Mattis scale) and behaviour (Ardouin scale) were assessed before surgery and one year after. RESULTS: Before surgery, whereas cognitive and motor assessments where similar between groups, dopamine agonist (but not levodopa) dosages were higher in creative patients (p=0.01). The Ardouin scale revealed also a specific psycho-behavioural profile of creative patients which had higher scores for mania (p< 0.001), hobbyism (p=0.001), nocturnal hyperactivity (p=0.041), appetitive functioning (p=0.003) and ON euphoria (p=0.007) and lower scores for apathy and OFF dysphoria (p=0.04 for each). Postoperative motor, cognitive and behavioural scores as dopaminergic treatment dosages were equivalent between groups. Motor improvement allowed for a 68.6% decrease in dopaminergic treatment. Only one of the 11 patients remained creative after surgery. Reduction of dopamine agonist was significantly correlated to the decrease in creativity in the whole population of study (Spearman correlation coefficient ρ =0.47 with confidence index of 95% = [0.16;0.70], p=0.0053). CONCLUSION: Creativity in PD is linked to dopamine agonist therapy, and tends to disappear after STN DBS in parallel to reduction of dopamine agonists, which are relatively selective for the mesolimbic D3 dopamine receptors